Nutrient Cycling in Eucalyptus globulus Plantation II. Litter Production and Nutrients Return - George, M.; Varghese, G. (Indian Forester, 1990)
Litter production and nutrients in Eucalyptus globulus plantation of age 10 years were studied for a period of one year. A total of 8492 kg/ha of litter was produced of which leaf litter contributed 40% (3402 kg/ha), twig 38% (3187 kg/ha) and bark 22% (1903 kg/ha) With reeards to nutrients. The highest concentration of N, P and K was in leaf. On an annual basis, the total return of nitrogen was 58 kg/ha followed by potassium 40 kg/ha and phosphorus 4.6 kg/ha. Maximum amoust of all the nutrients were returned thorugh litter and lowest through bark.